PELAKSANAAN PERJANJIAN ANTARA PTPN XIII DENGAN PETANI PLASMA DI PONTINAK - Jeremia Ramot Liseseli Sitorus; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
According to Article 1234 of the Civil Code, debtors are required to submit achievements to creditors where achievements in the form of giving, acting, or not doing anything. In the event that the debtor is unable to fulfill the agreed upon achievements, this is called default. The author is interested in analyzing a case that occurred between PT Perkebunan Nusantara XIII which is a state-owned company and plasma farmers through the Koperasi Taminses village of Menyabo, Tayan hulu sub-district, Sanggau district, West Kalimantan. Where there are defaults carried out by smallholders in terms of selling Fresh Fruit Bunches that are not in accordance with the agreement with PTPN XIII and payment of credit installments by farmers who do not comply with the agreement between the two parties. The author formulates the main problems to be discussed regarding How the implementation of the agreement between PTPN XIII and Plasma Farmers through the Taminses Cooperative in Menyabo Village, Tayan Hulu Sub-District, West Sanggau Kalimantann District and how efforts to resolve the default of plasma farmers to PTPN XIII. The research method used is sociological juridical research, because in this study the author directly conducted research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in Pontianak, while the population and samples were all parties related to the problems examined in this study. In data collection, the type of data used in this study are primary data and secondary data and tertiary data in the technique of collecting data in this study by interviewing and library research. From the results of the research conducted by the author in the agreement between PTPN XIII and Plasma Farmers, a default occurred by farmers, namely the sale of TBs and payment of credit installments that were not in accordance with the agreement. In implementing the agreement, farmers who process oil palm land produce production that is not in accordance with the production target, so farmers make sales outside the PTPN XIII factory to avoid paying credit installments.Keywords: Agreement - Engagement- Breach of Contract